The Knowledge and Attitude of Parents About the Dental Treatment of Their Children During the New Type of Coronavirus Outbreak in Northern Cyprus - Ekinci, Ayse; Tosun, Ozgur; Islam, Aylin (Frontiers in Public Health, 2022)
Background The aim of this study was to assess the knowledge and attitude of parents living in Northern Cyprus about the oral care and dental treatments of their children during the outbreak of the new type of Coronavirus (COVID-19). Methods An online self-administered questionnaire was conducted consisting of 33 questions. A total of 256 parents participated in this study. The questionnaire was divided into two parts. The first part consists of demographic information and the second part consists of the awareness and knowledge of parents about dental treatments during COVID-19. SPSS software was used for statistical data analysis. Results In total, 81.9% of the mothers and 59.6% of the fathers stated that their children could be infected with COVID-19 during dental treatments and were apprehensive about their children undergoing such treatment because of the outbreak. Participants were asked about their knowledge regarding the transmission of COVID-19 through air droplets during dental treatments and the findings revealed that mothers (89.5%) were more aware of this than fathers (77.2%). The majority of the participants (77%) stated that their children could become infected with COVID-19 during dental treatments and were apprehensive about their children undergoing such treatment because of the outbreak; however, 65.1% did not take any extra precautions regarding their children's oral health and care. Conclusion The majority of the parents in Northern Cyprus have good knowledge about dental clinics being one of the high-risk areas where COVID-19 can be transmitted by aerosols from infected people. However, further steps need to be taken to strengthen parents' motivations for home oral care and more studies are needed to assess the continuing impact of the COVID-19 pandemic on parents' attitudes toward and knowledge about dental procedures.